Real-time optimisation of large river and reservoir system operations - Madsen, Henrik (IAHR, 2020)
We present a new approach for real-time optimisation of large river and reservoir systems that combines physically-based hydrological-hydrodynamic models with surrogate control models within a Model Predictive Control framework. The approach is demonstrated in the optimisation of storage operations of the Murrumbidgee River system in New South Wales, Australia. This system consists of multiple reservoirs with pronounced travel times between the reservoirs. The test shows a large potential for improving operational efficiency of large water systems.